Features of Cellular Link of Immune Response in School-Age Children with Late-Onset Asthma Depending on Acetylation Polymorphism - U.I. Marusyk; I.U. Bezrukov (Zaslavsky O.Yu., 2016)
Background. Bronchial asthma is one of the most common diseases in the world, the number of patients with this disease is increasing, especially among children. They believe that the inefficiency of controlling asthma therapy, which is observed in almost half of patients, is due particularly to the presence of different asthma-phenotypes. Objective. To evaluate some indicators of cellular parts of the immune system in schoolchildren, considering acetylation phenotypes in order to optimize asthma control late-onset asthma. Materials and methods. In pulmonology unit of Chernivtsi Regional Child Clinical Hospital there were examined 72 schoolchildren with late-onset asthma (disease first manifested at the age of 6 years old). By the course of the disease children were divided into two clinical groups. The first group included 34 patients with slow type of acetylation (mean percentage of acetylated sulfadimidine in urine was less than 75.0 %). The second clinical group was formed by 38 students with fast type of acetylation (mean percentage of acetylated sulfadimedin in urine was more than 75.0 %). Blood T-lymphocytes, T-helper cells and T killer/suppressor and B-lymphocytes were tested in all children by immunofluorescent assay method using a set of monoclonal antibodies. Results. The slow type of acetylation in children with late-onset asthma almost triple increased risk of CD3 decline in peripheral blood. Every second child (54.1 ± 10.1 %) with the slow type of acetylation and late-onset asthma had reduced CD8 level (less than 18.0 g/l), while in the comparison group only 21.0 ± 9.3 % of patients had decreased concentration (P < 0.05). Conclusion. In the most patients with slow type of acetylation course of late-onset asthma was associated with a decrease in CD3, CD4, CD8 levels in peripheral blood and B-lymphocytes, that indirectly indicates the severity of chronic inflammatory allergic process in this cohort of persons and the exhaustion of the body.